The effect of Social Economic Factors on Ability to Save of Farmers: the role of Income Supply, Education Supply, Experience, Age, Land Area Distribution, Piece, Consumption and Family - Muhammad Buhari Sibuea; Faiz Ahmad Sibuea (International Journal of Supply Chain Management, 2020)
The ability of farmers in the village's economic life is very varied and tends to be in a weak position, especially in terms of saving skills. This study aims to determine the influence of socioeconomic factors on the ability to save, pull, and push elements of farmers to keep and resource savings fund farmers. This research is a case study in Deli Serdang Regency, North Sumatera, where 60 people from 312 populations of paddy rice farmers were sampled purposively. The results showed that simultaneously social factors: the number of dependents, education supply, experience, and age of farmers significantly affected the ability to save. While partially, the number of dependents and skills influence substantially the ability to save, while the education supply and age of the farmer have no significant effect on the ability to save. Simultaneously economic factors: land area distribution, income supply, price, and consumption have a substantial impact on the ability to save. Partially, use has a significant effect on the ability to save, while land area distribution, income supply, and the price has no significant impact on the ability to save. The factors attracting farmers to keep are security, the interest of money, prizes, proximity to their homes, and familiarity with bank officers. While the elements are driving farmers to save the desire to change lives, children's education supply expands the business, supplies sudden necessities, and insurance. Source of farmers' savings comes from farm income supply, off-farm income supply, and other family income supply. The study recommends that farmers increase their farming skills to better earnings so that the ability to save the better. Farmers can utilize existing financial institutions as much as possible for farming needs.